Les démoniaques dans l'art: Charcot and the “hysterical saints” - Coutinho, Léo; Caeira, Marlon Wycliff; Paola, Luciano de; Walusinski, Olivier; Cardoso, Francisco Eduardo Costa; Lima, Plinio Marcos Garcia de; Teive, Hélio A. Ghizoni (Arquivos de Neuro-Psiquiatria, 2022)
Professor Jean-Martin Charcot was the founder of clinical neurology and one of the prominent researchers in the field of hysteria in the 19th century. His book Les démoniaques dans l'art is a representation of hysterical symptoms in religion and religious art. This paper aims to discuss Charcot's descriptions of hysteria in religion and his “hysterical saints”.Professor Jean-Martin Charcot foi o fundador da neurologia clínica e um dos pesquisadores mais proeminentes no campo da histeria durante o século XIX. Seu livro Les démoniaques dans l'art é uma representação dos sintomas histéricos na religião e arte religiosa. Esse artigo objetiva discutir as descrições de Charcot de histeria na religião e seus “santos histéricos”.
Keywords: Hysteria; History of Medicine; Religion and Medicine; Art; Epilepsy